Răspuns :
a + b = 3 x ( a - b)
a + b = 3 a - 3 b
a - 3 a = -3 b - b
- 2 a = - 4 b
2 a = 4 b l : 2
a = 2 b
a + b = 2 b + b = 3 b
3 b : b = 3
a + b > b de 3 ori
a + b = 3 a - 3 b
a - 3 a = -3 b - b
- 2 a = - 4 b
2 a = 4 b l : 2
a = 2 b
a + b = 2 b + b = 3 b
3 b : b = 3
a + b > b de 3 ori
a+b=3a-3b
Acum grupam termenii
l=>2a=4b
l=>a=4b/2
l=>a=2b
Inlocuim in prima formula
l=>a+b=3b
l=>Suma este de 3 ori mai mare ;
Acum grupam termenii
l=>2a=4b
l=>a=4b/2
l=>a=2b
Inlocuim in prima formula
l=>a+b=3b
l=>Suma este de 3 ori mai mare ;